Effect of Early Continuous Veno-Venous Haemofiltration in Severe Acute Pancreatitis for the Prevention of Local Pancreatic Complications - Satish Chandra Yadav; Bingqiang Zhang (Gastroenterology Research and Practice)
Objective. To compare the conventional treatment and continuous veno-venous haemofiltration (CVVH) in severe acute pancreatitis (SAP) for the prevention of pseudocyst and walled-off necrosis. Patients and Methods. Forty-two patients were divided into two treatment groups: conventional treatment group contained 24 patients and CVVH had 18. Conventional treatment group patients were treated symptomatically and according to the causes. CVVH group patients were treated symptomatically, and CVVH was done within 2 hours of admission. Results. In both groups, there was a decrease in amylase, lipase, CRP, IL-6, IL-10, TNF-alpha, Ranson score, Balthazar score, and APACHE-II score after 72 hours, but the decrease was significantly greater in CVVH patients. There were no any local pancreatic complications in CVVH patients, but 1 patient had an acute peripancreatic fluid collection, 2 patients had pseudocyst, and 2 patients had walled-off necrosis (WON), and a mortality one was seen in the conventional treatment group. Conclusion. The present study shows that early CVVH may be able to prevent the formation of pseudocyst and win in SAP patients.